Algonquin-Nipissing Shorelines, North Bay, Ontario - Karrow, Paul (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThe general extent, outlet location at North Bay, and shoreline tilt pattern of glacial Lake Algonquin were established by Spencer, Gilbert, Taylor, and Goldthwait about a century ago. Chapman and Harrison in the mid 1900s identified several eastward outlets and suggested correlations to named water planes as retreating ice lowered Algonquin levels. The present work supplements the meagre available North Bay shoreline elevation data with about 30 new points. Probable Cedar Point, Payette, Sheguiandah, and Korah shorelines are identified; several lower levels have no known outlets. Algonquin shoreline tilts are about 1.4 metres per kilometre. Using Nipissing shoreline elevations for correlation, North Bay data are compared with Sudbury data, showing closely similar trends, but with offsets of Algonquin shorelines probably attributable to errors from 120‑kilometre-long projections and 5 000‑year changes in uplift pattern. Of 24 radiocarbon dates compiled from the literature, 16 are on gyttja. Some of these incorporate old carbon error and require further testing with dates on terrestrial plant macrofossils. Available data remain sparse and require more basic mapping to improve ice-margin/shoreline correlations near the outlet area.